Severity of inattention symptoms, experiences of being bullied, and school anxiety as mediators in the association between excessive short-form video viewing and school refusal behaviors in adolescents - Du, Yuru; Wang, Jianqiang; Wang, Ziyan; Liu, Jiuying; Li, Shaoxiong; Lv, Jing; Peng, Yuhan; Chang, Shining; Li, Miaomiao; Liu, Huan; Liu, Xuan; Yu, Xuezhu; et al. (Frontiers in Public Health, 2024)
Background: Recent years have seen an increase in school refusal behavior among adolescents, potentially due to factors like excessive short-form video viewing, bullying, and school anxiety.Limited research has investigated how these factors contribute to school refusal behavior. This study used random forest regression, path analysis, and network analysis to identify key variables and pathways leading to school refusal behavior.In this cross-sectional questionnaire-based study, 2056 (996 male, 1060 female, mean age: 14.79 ± 1.24 years) middle and senior high school students were asked to complete the School Refusal Behavior Assessment questionnaire to assess school refusal behavior features, the Excessive Short-Form Video Viewing Scale as well as self-reported viewing times during leisure days to assess excessive short-form video viewing, the SNAP-IV Rating Scale to assess the severity of inattention symptoms, and the self-administered questionnaires to assess experiences of being bullied and school anxiety.The prevalence of school refusal behavior in the surveyed adolescents was found to be 31.9% (95% confidence interval (CI): 29.8%-33.9%). In terms of significance, the severity of